Analysis of STEM-Based Student Worksheet Development with Scaffolding using the Web - Eva Novrianti Boang Manalu; Menza Hendri; Dian Pertiwi Rasmi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to analyze the needs of teachers and students on the development of learning media in the form of STEM-based student worksheets with scaffolding using the web. The development is carried out using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data obtained through interviews submitted to teachers. Teachers need an interesting learning media and can help students understand the material. While students need learning media that can help students towards understanding concepts. So that researchers will develop student worksheets using the web. Products produced in web form and based on STEM with Scaffolding